Mapping atonement : the doctrine of reconciliation in Christian history and theology - Witt, William G., 1955-; Scandrett, Joel (Grand Rapids Baker Academic, 2022)
"This introduction traces the origins, development, and divergent streams of atonement theology throughout the Christian tradition and proposes key criteria by which we can assess their value"--
Includes bibliographical references (pages 227-236) and index.
Keywords: Atonement -- History of doctrines